Power Distribution Transformer Faults Diagnostic Skills: Case study at Electrical Engineering Technology Students of Polytechnics in North-East Nigeria - Medugu, Jimritu Dunama; Zambwa, Joseph; Bashir, Mohammed; Ibanga, Isaac John (Engineering Science Letter, 2023)
This study determined the power distribution transformer faults diagnostic skills needed by Electrical Engineering Technology students of polytechnics in North-East Nigeria. Three research questions and hypotheses guided the study, employing a descriptive survey research design. The study population was 144, comprising 135 Electrical Engineering Technology Lecturers, 3 Power Transformer Maintenance Technicians and 6 Electric Power Distribution Company-Based Supervisors. The entire population was used. Hence, there was no sampling. The instrument used for data collection was a structured questionnaire titled Power Distribution Transformer Faults Diagnostic Skills Questionnaire (PDTFDSQ) developed by the researchers. Three experts validated the instrument, and a reliability of 0.74 was obtained using the Cronbach Alpha reliability method. The mean statistic was used to answer the research questions, while ANOVA was used to test the null hypotheses of the study at a 0.05 level of significance. The study’s findings revealed that the Electrical Engineering Technology students of polytechnics in North-East Nigeria required fault diagnosis (troubleshooting) skills, ICT skills and safety skills. The study recommended that the Department of Electrical Engineering Technology in all polytechnics should endeavour to expose students to faulting-finding activities so that students of Electrical Engineering will acquire fault diagnosis (troubleshooting) skills for maintaining power distribution transformers.